2020
DOI: 10.1186/s12935-020-1148-8
|View full text |Cite
|
Sign up to set email alerts
|

The clinical prognostic value of lncRNA FAM83H-AS1 in cancer patients: a meta-analysis

Abstract: Background: Family with sequence similarity 83 member H antisense RNA 1 (FAM83H-AS1) is a novel long noncoding RNA. Increasing studies have reported that FAM83H-AS1 is abnormally expressed in a variety of tumors and is associated with poor outcome. However, the clinical prognostic significance of lncRNA FAM83H-AS1 in tumors is not completely known. Methods:In this meta-analysis, literature was collected up until February 5, 2020 through multifarious retrieval strategies by searching through electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…MIR31HG is a novel factor involved in melanoma progression ( 31 ). Increased expression of FAM83H-AS1 may predict poor prognosis in cancer patients ( 32 ). In this study, HCG11 was positively correlated with advanced stage and lymph node metastasis and negatively associated with NPC patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…MIR31HG is a novel factor involved in melanoma progression ( 31 ). Increased expression of FAM83H-AS1 may predict poor prognosis in cancer patients ( 32 ). In this study, HCG11 was positively correlated with advanced stage and lymph node metastasis and negatively associated with NPC patient survival.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, plenty of studies indicated that several lncRNAs may serve as a promising prognostic biomarker for cancer patients, such as SNHG1 [32], linc00152 [33], PCAT-1 [34], FAM83H-AS1 [35] and so on. And ZFAS1 is exactly one of them.…”
Section: Discussionmentioning
confidence: 99%
“…However, the diversified results, the heterogeneity of lncRNAs biology and prognosis, as well as the presence of different treatment options make the clinical decision-making process highly varied. Thus, a series of systematic reviews and meta-analyses have been conducted to provide further evidences on the relationship between variants of dysregulated lncRNAs and prognosis of cancer ( Chen C et al, 2018 ; Quan et al, 2018 ; Tian et al, 2018 ; Zhang S et al, 2020 ; Yang et al, 2020 ; Zhou et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%